Accountability of indosurya savings and loan cooperative in dealing with cases that harm investors - Eka Baharuddin; Muhammad Rizal; Tetty Herawati (Institute of Computer Science (IOCS), 2023)
This research aims to find out how the accountability of Indosurya savings and loan cooperative in handling fraud cases against its investors. This research uses descriptive method. The results of this study can be seen that the Indosurya savings and loan cooperative is not accountable in facing and resolving this case In terms of GCG principles including accountability, it can be said that the Indosurya case does not meet the expected standards. As an investor, it is important to always check the company's reputation before making an investment. This can be done by checking the company's financial statements, checking the company's track record, and checking the experience of other investors who have invested in the company.